Online Collaborative Learning - Paola Julie Aguilar Cruz; Zongping Xiang (Academia y Virtualidad, 2023)
Technology provides new learning environments in which 21st-century skills such as collaboration are involved, and English becomes the language of communication and interaction among participants. During the lockdown caused by the COVID-19 pandemic, students faced the shift from face-to-face to online classes, which made students feel demotivated and lost opportunities to use English in meaningful environments. This article reports a qualitative research process to explore students’ perceptions of an Online Collaborative Learning (OCL) project focused on story writing between China and Colombia. Accordingly, surveys and interviews were implemented to gather data from the 51 students and 12 English teachers that participated in the study. The 51 students were divided into six groups, and each group was assigned two coordinators: one from China and one from Colombia. This article contributes to knowledge in OCL and cross-cultural communication since it describes students’ strengths and difficulties when interacting with others whose first language is not English. Specifically, it is concluded that speakers of English as a foreign language deal with challenges and strengths related to time zone differences, English language proficiency, intrinsic motivation, and attitudes. It is also mentioned that teamwork skills, empathetic language, and the ability to use technology mediate the collaborative writing process.